Medición y cálculos de espectros de neutrones en agua liviana - Abbate, Máximo Julio; Volkis, J. E.; Lolich, J. V.; Remez, Luis Alberto (Asociación Física Argentina, 1973)
Fil: Abatte, M. J. Ejército Argentino; Argentina